1998
DOI: 10.1093/protein/11.12.1155
|View full text |Cite
|
Sign up to set email alerts
|

Sequence properties of GPI-anchored proteins near the omega-site: constraints for the polypeptide binding site of the putative transamidase

Abstract: Glycosylphosphatidylinositol (GPI) anchoring is a common post-translational modification of extracellular eukaryotic proteins. Attachment of the GPI moiety to the carboxyl terminus (omega-site) of the polypeptide occurs after proteolytic cleavage of a C-terminal propeptide. In this work, the sequence pattern for GPI-modification was analyzed in terms of physical amino acid properties based on a database analysis of annotated proprotein sequences. In addition to a refinement of previously described sequence sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
189
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(198 citation statements)
references
References 1 publication
8
189
0
1
Order By: Relevance
“…In general, we find that the big-PI predictor (18,19) produces scores that are reasonably well correlated with processing efficiency, although there are exceptions in both directions: some of our poorly processed mutants obtained a score superior to 4, e.g. rm24 and rm41 (HCGG), rm16 (ESEGR), and rm27 (EGGSR), while some mutants that obtained less than 1.5 were in fact comparable with the wild type, e.g.…”
Section: Fig 6 Analysis Of Mutants Containing Chimeric Gpi Additionmentioning
confidence: 74%
See 1 more Smart Citation
“…In general, we find that the big-PI predictor (18,19) produces scores that are reasonably well correlated with processing efficiency, although there are exceptions in both directions: some of our poorly processed mutants obtained a score superior to 4, e.g. rm24 and rm41 (HCGG), rm16 (ESEGR), and rm27 (EGGSR), while some mutants that obtained less than 1.5 were in fact comparable with the wild type, e.g.…”
Section: Fig 6 Analysis Of Mutants Containing Chimeric Gpi Additionmentioning
confidence: 74%
“…In addition, Caras and colleagues found that, for optimal processing, the site should be located between 10 and 12 residues upstream of the C-terminal hydrophobic sequence (10). A systematic analysis of all reported GPI-anchored proteins and of the effects of mutations in their C-terminal region has led Eisenhaber et al (18,19) to formulate a prediction algorithm, which confirmed that the volumes of the side chains located near the cleavage site exert a major influence, probably because they must be accommodated within the catalytic pocket of a transamidase (15). Several components of the transamidase complex have recently been cloned (20,21).…”
mentioning
confidence: 99%
“…The signal peptide was predicted with SignalP Version 3.0 (http:// www.cbs.dtu.dk/services/SignalP/) (Bendtsen et al 2004), and the hydrophobic profile was made using the Kyte-Doolittle method (Kyte and Doolittle 1982). GPI modification was predicted using Big-PI (http://mendel.imp.ac.at/gpi/gpi_ server.html) (Eisenhaber et al 1998). The phylogenetic tree was constructed with MEGA3.1 (Kumar et al 2004 (Hubbell et al 2002).…”
Section: Sequence and Phylogenetic Analysesmentioning
confidence: 99%
“…We performed in silico analysis for the predicted NTNG1 proteins concerning the possibility of a potential cleavage site for glycosylphosphatidylinositol (GPI) anchoring following the o ĂŸ 2 rule, 8 by using the DGPI website available at ExPASy Proteomics tools (www.expasy.org/tools/).…”
Section: In Silico Analysis Of Ntng1mentioning
confidence: 99%